Penerapan Latihan Range of Motion (ROM) Pasif terhadap Peningkatan Kekuatan Otot Ekstremitas pada Pasien dengan Kasus Stroke - Agusrianto Agusrianto; Nirva Rantesigi (Jurnal Ilmiah Kesehatan (JIKA), 2020)
Stroke is a condition that occurs when the blood supply to the brain is interrupted due to blockage or rupture of brain blood vessels with symptoms such as hemipareseis, slurred speech, difficulty walking, loss of balance and decreased muscle strength. The aim of knowing the application of passive Range of motion (ROM) exercises in non-hemorrhagic stroke patients with limb paralysis. This research method used a descriptive method with a case study approach in which one stroke patient was given passive ROM exercises. The results showed that data on decreased consciousness, BP 170/120 mm / Hg and decreased limb muscle strength. Nursing diagnosis of physical mobility impairment, the nursing intervention given was passive ROM exercises twice a day aimed at increasing muscle strength. Evaluation after six days of intervention, the patient could move his hands and feet. In the upper/ lower right limb from scale 2 to scale 3 and the upper / lower left limb from 0 to 1. The conclusion after being given passive ROM exercises, stroke patients experienced increased muscle strength in both extremities.